The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1212/nxi.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light chain predicts disease activity in relapsing-remitting MS

Abstract: Objective:To investigate whether serum neurofilament light chain (NF-L) and chitinase 3-like 1 (CHI3L1) predict disease activity in relapsing-remitting MS (RRMS).Methods:A cohort of 85 patients with RRMS were followed for 2 years (6 months without disease-modifying treatment and 18 months with interferon-beta 1a [IFNB-1a]). Expanded Disability Status Scale was scored at baseline and every 6 months thereafter. MRI was performed at baseline and monthly for 9 months and then at months 12 and 24. Serum samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
128
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 126 publications
(147 citation statements)
references
References 25 publications
10
128
2
Order By: Relevance
“…Shorter term studies have found correlations between new gadolinium‐enhancing lesions and serum NfL values 13, 15, 31. Patients with either brain, spinal, or both brain and spinal gadolinium‐enhancing lesions had higher serum NfL than those without 13.…”
Section: Discussionmentioning
confidence: 99%
“…Shorter term studies have found correlations between new gadolinium‐enhancing lesions and serum NfL values 13, 15, 31. Patients with either brain, spinal, or both brain and spinal gadolinium‐enhancing lesions had higher serum NfL than those without 13.…”
Section: Discussionmentioning
confidence: 99%
“…16 The concentration of NFL is elevated in the cerebrospinal fluid (CSF) of MS patients, 17 and it is reduced by effective immunomodulatory treatments such as fingolimod and natalizumab. 22,23 Only one observational study has so far addressed the relationship between vitamin D and NFL in MS, showing that high serum levels of 25-hydroxyvitamin D were associated with low CSF levels of NFL. 22,23 Only one observational study has so far addressed the relationship between vitamin D and NFL in MS, showing that high serum levels of 25-hydroxyvitamin D were associated with low CSF levels of NFL.…”
mentioning
confidence: 99%
“…18,19 The concentrations of NFL in serum and CSF are highly correlated, 20,21 and serum NFL also predicts inflammatory disease activity and brain and spinal cord atrophy. 22,23 Only one observational study has so far addressed the relationship between vitamin D and NFL in MS, showing that high serum levels of 25-hydroxyvitamin D were associated with low CSF levels of NFL. 24 We have previously performed a randomized placebo-controlled trial (RCT) of weekly administration of 20 000 IU vitamin D3 in fully ambulatory patients with RRMS living above the Arctic Circle (NCT00785473).…”
mentioning
confidence: 99%
“…The ratio between plasma and CSF in our study was of the same magnitude as in earlier findings. 22 Our study did not have the prerequisites to explore such aspects further. A recent publication, using serum NFL as a tool for individual follow-up, demonstrated that there was a moderate increased odds ratio of 1.5 of the occurrence of a Gd-positive lesion if an increase of 10 pg/mL in s-NFL was detected.…”
Section: Discussionmentioning
confidence: 95%
“…A recent publication, using serum NFL as a tool for individual follow-up, demonstrated that there was a moderate increased odds ratio of 1.5 of the occurrence of a Gd-positive lesion if an increase of 10 pg/mL in s-NFL was detected. 22 Our study did not have the prerequisites to explore such aspects further.…”
Section: Discussionmentioning
confidence: 95%